2021
DOI: 10.1038/s41598-021-83290-1
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical aspects of seeds from Cannabis sativa L. plants grown in a mountain environment

Abstract: Cannabis sativa L. (hemp) is a versatile plant which can adapt to various environmental conditions. Hempseeds provide high quality lipids, mainly represented by polyunsaturated acids, and highly digestible proteins rich of essential aminoacids. Hempseed composition can vary according to plant genotype, but other factors such as agronomic and climatic conditions can affect the presence of nutraceutic compounds. In this research, seeds from two cultivars of C. sativa (Futura 75 and Finola) grown in a mountain en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…Cannabis can be classified into two main chemotypes based on its THC/CBD ratio. By consensus, industrial cannabis has a low THC content (< 0.2%) with a THC/CBD ratio lower than 1, while non-industrial cannabis, also called drug-type, has high THC values (> 0.2%) with a ratio greater than 1 (Cattaneo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Cannabis can be classified into two main chemotypes based on its THC/CBD ratio. By consensus, industrial cannabis has a low THC content (< 0.2%) with a THC/CBD ratio lower than 1, while non-industrial cannabis, also called drug-type, has high THC values (> 0.2%) with a ratio greater than 1 (Cattaneo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolome analysis showed that 236 metabolites were differentially accumulated in two local hemp seed breeding varieties with different dimensions in India ( Rashid et al, 2021 ). Being planted in the mountain environment greatly affects the fatty acids profile and carotenoids content of hemp seeds ( Cattaneo et al, 2021 ). Proteomic signatures also indicated that there are differences between two hemp seed varieties ( Park et al, 2012 ; Aiello et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Albumin, majorly edestin, makes up a higher proportion of the protein content of hempseed (60%–80%) while the rest of the protein content is globulin (House et al, 2010). Similarly, hempseed is rich in polyunsaturated fatty acids (Cattaneo et al, 2021; Razmaitė et al, 2021), and consumption of a hempseed‐supplemented diet was shown to increase the breast milk quality of dairy goat (Rapetti et al, 2021). Similarly, hempseed oil protected Drosophila melanogaster larvae from experimentally‐induced oxidative stress (Vitorović et al, 2021) and improved the nutritional and immune profile of offspring of piglets fed hempseed oil‐supplemented diet (Vodolazska & Lauridsen, 2020).…”
Section: Introductionmentioning
confidence: 99%